Análisis de contenido de los periódicos rurales de la Regional no. 1 del Instituto Colombiano Agropecuario ICA. - Rodríguez Pérez, Pablo Guillermo (Instituto Colombiano Agropecuario, 1982)
Maestría en Ciencias